Kidney nonprocurement in solid organ donors in the United States. Issue 12 (16th May 2020) - Yu, Kathleen; King, Kristen; Husain, Syed A.; Dube, Geoffrey K.; Stevens, Jacob S.; Ratner, Lloyd E.; Cooper, Matthew; Parikh, Chirag R.; Mohan, Sumit
Abstract : There are limited data on the nonprocurement of kidneys from solid organ donors. Analysis of Standard Transplant Analysis and Research files was undertaken on all deceased donors in the United States with at least 1 solid organ recovered. From 2000 to 2018, 21 731 deceased donor kidneys (averaging 1144 kidneys per year) were not procured. No kidneys were procured from 8% of liver donors, 3% of heart donors, and 3% of lung donors. Compared to donors with all kidneys procured, those with none procured were older and more likely obese, black, hypertensive, diabetic, hepatitis C positive, smokers, Public Health Service – Increased Risk designated, deceased after cardiac death, or deceased after cerebrovascular accident. Although these donors had lower quality kidneys (median Kidney Donor Risk Index (interquartile range) 1.9 (1.0) vs 1.2 (0.7)), there was substantial overlap in quality between nonprocured and procured kidneys. Nearly one third of nonprocurements were attributed to donor history. Donors with elevated terminal creatinine likely resulting from acute kidney injury (AKI) had higher odds of kidney nonprocurement. Nonprocurement odds varied widely across Organ Procurement and Transplantation Network regions, with a positive correlation between donor kidney nonprocurements and kidney discards at the donation service area level. These findings suggest current discard rates underestimate the underutilization of deceased donor kidneys and more research is needed to optimize safe procurement and utilization of kidneys from donors with AKI. Abstract : In this analysis of deceased donors in the United States between 2000–2018, the authors show that kidney nonprocurement, despite procurement of a lung, heart, or liver, was associated with donor history and elevated terminal creatinine that likely reflect donor acute kidney injury.